How do citizens with low health insurance literacy choose a health insurance policy in the Netherlands? An interview study - Laurens Holst; Anne Brabers; Jany Rademakers; Judith de Jong (BMC Health Services Research)
Abstract Various countries have implemented a choice-based health insurance system. For such systems to function as intended, it is crucial that all citizens have the opportunity to make well-informed decisions with regard to their health insurance policy. There is, however, ample research evidence to suggest that many citizens may lack the required skills to do so, thus increasing the likelihood of suboptimal insurance choices and incurring unexpected costs. The current study explored what barriers citizens in the Netherlands, with low health insurance literacy (HIL), face when selecting a health insurance policy, and what their specific needs and preferences are regarding information and support. Semi-structured interviews (online or telephone) were performed between January 2023 and April 2023 among sixteen with a low level of HIL. The data were analyzed using thematic analysis methods. Our results show that not all citizens with low HIL are sufficiently motivated to actively look for alternative health insurance options every year. This is partly due to the feeling that it is a task imposed upon them by the government, and because choosing a health insurance policy is perceived as too complicated and not sufficiently worthwhile. There is a need among citizens with low HIL for clear and practical information about health insurance policies, especially from the government and health insurers. In addition to this need, we recommend enhancing awareness regarding the consequences of neglecting to explore such health insurance options. Moreover, more personal attention for the process of selecting a health insurance policy should be offered to vulnerable groups such as those who possess insufficient digital skills.